2013
DOI: 10.1007/s10973-013-3246-5
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of elastic properties and thermal conductivity of Al2O3/h-BN composites

Abstract: The presence of h-BN phase in the composites, in which it is fulfilling a role of a solid lubricant, causes the appearance of the anisotropy of the elastic properties and thermal properties. In order to assess the extent of the phenomenon, velocity changes of ultrasonic wave propagation were measured and thermal conductivity changes were researched. Measurements were carried out on composites of alumina matrix, which had h-BN introduced in an amount of 0-30 vol.%. The study included measurements of the speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
5
8
0
Order By: Relevance
“…5). This situation is similar to the h-BN orientation in hot-pressed Al 2 O 3 /h-BN composites [17]. It can have a very important influence on thermal conductivity of the composites, which will be presented in this study.…”
Section: Resultssupporting
confidence: 69%
“…5). This situation is similar to the h-BN orientation in hot-pressed Al 2 O 3 /h-BN composites [17]. It can have a very important influence on thermal conductivity of the composites, which will be presented in this study.…”
Section: Resultssupporting
confidence: 69%
“…Room temperature mechanical properties of Al 2 O 3 /h-BN refractories samples were investigated, and the results are depicted in Table II. The results show that fracture strength r f , Young's modulus E, fracture toughness K IC , and work of fracture c WOF were all decreased with the increase of h-BN content fraction, as also observed by Rutkowski et al [19] and Kusunose et al [31] The mechanical properties were closely associated with the physical properties such as AP and BD. The variation trend of the BD was same as that of the mechanical properties and these observations were in accordance with previous studies.…”
Section: A the Phase Composition And Microstructuresupporting
confidence: 77%
“…They claimed excellent machinability, high strength, high strain tolerance, and low Young's modulus, which were attributed to the weak gain boundaries. Rutkowski et al [19] reported that the materials with different amount of h-BN phases showed a decrease in relative density, Young's modulus, and thermal conductivity with the increase of volume fraction of h-BN dispersed in Al 2 O 3 matrix. However, no data concerning correlation between mechanical properties and TSR of this kind of material were found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This situation can lead to the anisotropy of heat transport of ceramic matrix composites. In the case of hexagonal boron nitride dispersed phase, the thermal properties (conductivity) decrease in all of directions in comparison with reference pure material [23]. It is caused mostly by agglomeration of hexagonal boron nitride particles, where the agglomerates are porous.…”
Section: Introductionmentioning
confidence: 91%
“…The uniaxial pressing, which helps to densify the materials during the sintering, becomes a problem for ceramic-2D phase materials. The one direction of applied pressure causes the orientation of two-dimensional phase in the ceramic matrix [23,24]. This situation can lead to the anisotropy of heat transport of ceramic matrix composites.…”
Section: Introductionmentioning
confidence: 99%